Use of dried blood spots and inductively coupled plasma mass spectrometry for multi-element determination in blood - Vacchina, Véronique; Huin, Vincent; Hulo, Sébastien; Cuny, Damien; Broly, Franck; Renom, Gilles; Perini, Jean-Marc (Journal of trace elements in medicine and biology, 2014)
The paper describes the development of an inductively coupled plasma mass spectrometry (ICP MS) method for multitrace element determination in dried blood spots (DBSs). The analytical conditions were optimized using Seronorm™ L-3 and L-1 Certified Reference Materials. The best results were obtained by sampling blood drops on a decontaminated PVDF filter membrane. After drying under metal-free conditions, the DBSs underwent acidic digestion and were analyzed with ICP MS. The method was then validated for As, Cd, Cu, Pb, Mo, Se and Zn. Using a matrix-matched calibration curve, the recovery levels ranged from 96% to 117%. The repeatability and reproducibility were generally below 15%. Limits of quantification ranging from 0.5 to 50μg/L. In order to investigate the analytical procedure under real sampling conditions, the results obtained from DBSs and liquid blood aliquots (less subject to contamination) from two adult subjects were compared.